Molecular modeling studies on the interactions of 7-methoxytacrine-4-pyridinealdoxime, 4-PA, 2-PAM, and obidoxime with VX-inhibited human acetylcholinesterase: a near attack conformation approach - da Silva, Jorge Alberto Valle; Nepovimova, Eugenie; Ramalho, Teodorico Castro; Kuca, Kamil; Celmar Costa França, Tanos (Journal of enzyme inhibition and medicinal chemistry, 2019)
7-methoxytacrine-4-pyridinealdoxime (7-MEOTA-4-PA, named hybrid 5C) is a compound formerly synthesized and evaluated in vitro, together with 4-pyridine aldoxime (4-PA) and commercial reactivators of acetylcholinesterase (AChE). This compound was designed with the purpose of being a prophylactic reactivator, capable of interacting with different subdomains of the active site of AChE. To investigate these interactions, theoretical results from docking were first compared with experimental data of hybrid 5C, 4-PA, and two commercial oximes, on the reactivation of human AChE (HssAChE) inhibited by VX. Then, further docking studies, molecular dynamics simulations, and molecular mechanics Poisson-Boltzmann surface area calculations, were carried out to investigate reactivation performances, considering the near attack conformation (NAC) approach, prior to the nucleophilic substitution mechanism. Our results helped to elucidate the interactions of such molecules with the different subdomains of the active site of HssAChE. Additionally, NAC poses of each oxime were suggested for further theoretical studies on the reactivation reaction.
Keywords: Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Acetylcholinesterase; Models, Molecular; cholinesterasové inhibitory; acetylcholinesterasa; Organothiophosphorus Compounds; obidoxim chlorid; Pralidoxime Compounds; VX; Cholinesterase Inhibitors; Pyridines; 7-MEOTA-4-PA; pyridiny; Oximes; Obidoxime Chloride; organothiofosforové sloučeniny; molekulární modely; NAC; molecular modeling; vztahy mezi strukturou a aktivitou; Humans; pralidoximové sloučeniny; molekulární struktura; Structure-Activity Relationship; oximy; lidé; Molecular Structure